Development and validation of the mpox stigma scale (MSS) and mpox knowledge scale (MKS) - Henna Budhwani; Ibrahim Yigit; Jacob B. Stocks; Marie C.D. Stoner; Erica Browne; Audrey E. Pettifor; Lisa B. Hightow-Weidman (BMC, 2024)
Abstract Background Few validated brief scales are available to measure constructs that may hinder mpox-related prevention and care engagement, such as knowledge and stigma. Both are highly salient barriers to infectious disease care and disease understanding, precursors to evaluating one's risk and need to, for example, accept vaccination. To address this gap, we developed and validated the Mpox Stigma Scale (MSS) and Mpox Knowledge Scale (MKS). Methods As part of a full-scale clinical trial, we offered an optional mpox survey to participants who self-identified as African American or Black, were 18-29 years old, and lived in Alabama, Georgia, or North Carolina (2023, N = 330). We calculated psychometric properties through confirmatory factor analyses (CFA) and applied Comparative Fit Index (CFI), Goodness of Fit Index (GFI), and Tucker-Lewis Index (TLI) values equal to or exceeding 0.90 and Root Mean Square Error of Approximation (RMSEA) and Standardized Root Mean Square Residual (SRMR) values less than 0.08 to determine adequate model fit. We computed internal reliability using Cronbach's alpha and calculated Pearson or Spearman correlation coefficients between the MSS and MKS and related variables. Results For the MSS, CFA results showed that the one-factor model fit the data well (χ2(df = 5, N = 330) = 34.962, CFI = 0.97, GFI = 0.99, TLI = 0.94, RMSEA = 0.13, SRMR = 0.03). For the MKS, the one-factor model provided a good fit to the data (χ2(df = 6, N = 330) = 8.44, CFI = 0.99, GFI = 0.99, TLI = 0.95, RMSEA = 0.15, SRMR = 0.02). Cronbach's alphas were MSS = 0.91 and MKS = 0.83, suggesting good to excellent reliability. The MSS was correlated with the MKS (r = .55, p < .001), stigmatizing attitudes (r = .24, p < .001), attitudes towards mpox vaccination (r=-.12, p = .030), and worry about contracting mpox (r = .44, p < .001). The MKS was correlated with worry about contracting mpox (r = .30, p < .001) and mpox disclosure (r=-.16, p = .003). Conclusions The MSS and MKS are reliable and valid tools for public health practice, treatment and prevention research, and behavioral science. Further validation is warranted across populations and geographic locations. Trial Registration ClinicalTrials.gov NCT05490329.